MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN MELALUI SENAM IRAMA DI KB TUNAS BANGSA DESA NAGA BERALIH KECAMATAN KAMPAR UTARA - Amat Hidayat; Dessy Heriyani; Melvi Lesmana Alim; Yolanda Pahrul (LPPM Universitas Bina Bangsa, 2022)
This study aims to improve the gross motor skills of children aged 4-5 years through rhythmic gymnastics at KB Tunas Bangsa Naga Switch Village, North Kampar District. The type of research is Classroom Action Research which is carried out collaboratively between researchers and classroom teachers. This research consisted of two cycles and each cycle was conducted in two meetings. The subjects of this study were 10 children of the Tunas Bangsa Playgroup (KB) in Naga Beralih Village, North Kampar District, which consisted of 6 boys and 4 girls. Data collection techniques through observation and documentation. The instruments used in this study were observation sheets and documentation. Techniques Data analysis was carried out in a qualitative descriptive manner. The results showed that there was an increase in gross motor skills after using rhythmic gymnastics. The child's gross motoric improvement every cycle experiences development. This is evidenced from the results of research 7 out of 10 children or 70% of the total have been able to do rhythmic gymnastics and begin to proficiently move their bodies without the help of their teachers